The Influence of Work Flexibility and Work-Life Balance on Employee Performance - Hediningrum, Windy Wahyu (Talent: Journal of Economics and Business, 2023)
This research aims to find out how much influence work flexibility and work-life balance have on employee performance at PT. Indonesia Epson Industry. The method used is a survey method, namely a quantitative survey research method carried out by distributing questionnaires which include statements regarding the issues of work flexibility, work-life balance and employee performance. This research took samples from PT. Indonesia Epson Industry received 80 respondents. The results of this research found that work flexibility does not have a significant effect on employee performance and work-life balance has a positive influence on employee performance.